Manajemen Sumber Daya Manusia Islam: Sejarah, Nilai, dan Benturan - Ihsan Rahmat; Netta Agusti (Institut Agama Islam Negeri Bengkulu, 2018)
Human resource management (HRM) in Western perspectives continue to be questioned in the East, especially from Islamic academics. There is hope to implement religious teachings in the organizational sphere. Generally, this paper discusses issues in Islamic HRM, questioning the extent to which Islam (text and context) governs people in organizations. Putting forward the literature sourced from the pages of Ebsco and Emerald using the keywords